GEJALA LANJUTAN PASIEN LANSIA KOMORBID PASCA COVID-19 DI KECAMATAN PABUARAN KABUPATEN CIREBON - haifa nabilah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
In January 2021, Pabuaran District had a total of 58 cases, 48 people were declared cured, 6 people died and 4 others are still under monitoring or isolation. The highest cases fell at the age of 46-59 years, which was around 36% with a total of 21 people. Of the total elderly confirmed positive for Covid-19, 52% have comorbid diseases, namely 11 people. In April 2021, 5 comorbid elderly patients complained that they had continued symptoms after Covid-19. With the appearance of these symptoms, it can increase and prolong the morbidity rate and increase the isolation time for patients. The general purpose of this study was to find out how the advanced symptoms by the elderly after Covid-19 in Pabuaran District, Cirebon Regency.This type of research is analytic observational with a descriptive design. Data analysis used information obtained from in-depth interviews. The informants of this study were Pabuaran Health Center surveillance officers, elderly patients with comorbidities who had advanced post-Covid-19 disease who were taken by purposive sampling technique and one of the patients' families. Data were collected using interviews and observations with in-depth interviews, field notes, and recording devices. Data analysis was carried out by descriptive analysis, selecting core items or keywords, reducing data, presenting data, and leveraging data. Keywords: Elderly, Comorbid, Advanced Symptoms, Rehabilitation